Essential Thrombocythemia in Young Women - Anggit Pungkas Wibowo; Eifel Faheri (HM Publisher, 2023)
Background: Essential thrombocythemia (ET) is a rare disease in which there is an increase in the platelet count of more than 450,000/mm3. An increase in the number of platelets occurs due to increased proliferation of megakaryocyte series. Although there is an increase in the number of platelets in ET, it has impaired function. ET clinical manifestations in 50% of cases are asymptomatic, but in symptomatic cases can be vascular occlusive events or microvascular thrombosis. Case presentation: A 22-year-old woman with complaints of rash on the hands and feet. Physical examination found an enlarged spleen in Schuffner 1 and ecchymosis on the arms and legs, a platelet count of 811,000/mm3. The peripheral blood smear shows large platelets, the bone marrow picture shows megakaryocytes, which are very easy to find, the size varies with sufficient platelet emission, the JAK2 gene mutation examination shows mutation detection, while the BCR-ABL gene mutation results do not detect gene fusion. Treatment is given cytoreductive therapy in the form of hydroxyurea, while acetylsalicylic acid is not given because there are contraindications for administration. Conclusion: Essential thrombocythemia is a neoplastic proliferative disease that occurs in the megakaryocyte series. The diagnosis of ET mostly found mutations in the JAK2 gene. ET management according to risk classification, where acetylsalicylic acid can be given very low and low risk, while intermediate and high risk can be given cytoreductive therapy.